Anthropometry dimensions of older Malaysians: comparison of age, gender and ethnicity - Mohd Yusuff, Rosnah; Hussain, Mohd Rizal; Syed Abdul Rashid, Sharifah Norazizan (Canadian Center of Science and Education, 2009)
Studies have indicated that body dimensions differ for various populations. To determine whether there are differences in the anthropometric data of the elderly population in Malaysia, the anthropometric data collected from a previous project was used. These comparisons can give some indications of the relative sizes between age, gender and ethnicity in Malaysian elderly populations. The results showed that some anthropometric dimensions were influenced by age, gender and ethnicity. Regression analysis showed that age and ethnicity were significant predictors (p< .01) of Malaysians elderly BMI’s. The analysis has provided important information in designing and planning of facilities and products for elderly populations.